PMO-069 Line sepsis rates are significantly improved in parenteral nutrition patients by having a nutrition nurse. (28th May 2012) - Tsakok, T; Blaker, P; Patel, K; O'Sullivan, S; Doherty, A; Morris, H; Dunn, J; McCarthy, M
Abstract : Introduction: Recent UK NCEPOD data highlights catheter line sepsis as a major complication of Parenteral Nutrition (PN). We hypothesise that a Specialist Nutrition Nurse may improve line sepsis rates by educating ward staff on line care. Our aim was to evaluate line complications in patients treated at Guy's & St Thomas' Hospitals before and after this intervention. Methods: Prospective dual-centre cohort study of patients started on PN over two 12-month periods (2005; 2010). Clinical data collected via pro forma, microbiology data via Electronic Patient Records. Results: 221 patients were recruited (141 in 2010, 80 in 2005). From the 2010 cohort, 90 were ward-based, 57 on ICU. Duration of PN ranged from 1 to 171 days (mean 17). Access was established by central line (65%) or peripherally-inserted central (PICC) lines (35%). Use of PICC lines had increased since 2005 (84% central vs 16% PICC). The incidence of line sepsis was significantly lower in 2010 than in 2005 (11% vs 31%, Fisher's test p=0.0002). In 2010 9/15 cases of line sepsis were confirmed by blood/line tip culture. Line complications were more likely to occur in patients on wards than ICU (34% vs 2%, Fisher's test p<0.0001). By contrast, rates of confirmed line sepsis were not significantly influenced by line type (Fisher's test p=0.5). Conclusion: This dual-centre audit demonstrates a significant reduction in catheter-related sepsis between 2005 (31%) and 2010 (11%). This is likely due to the introduction of a Nutrition Nurse to facilitate monitoring and line care in PN patients. The discrepancy in line sepsis rates between wards and ICU indicates that there is still scope to improve line care on wards. Increased use of peripherally-inserted feeding lines has had no impact on line sepsis rates. Competing interests: None declared. Reference: 1. Stewart JAD, Mason DG, Smith N, et al. A mixed bag—an enquiry into the care of hospital patients receiving parenteral nutrition. NCEPOD, 2010.